Multiple synchronous primary malignant neoplasms of renal, ureter and urinary bladder: a case report - Huang, Bincheng; Yin, Wenhui; Al-Qaisi, Mohammed Abdulkarem; Tian, Haifu; Zhao, Mengmeng; Zhang, Jin; Deng, Chaodan; Li, Na; He, Rui; Li, Guangyong (Frontiers in Oncology, 2025)
Synchronous multiple primary malignant neoplasms (MPMNs) involving distinct histopathological entities within the upper urinary tract represent a rare clinical phenomenon. We present a novel case of a 57-year-old male presenting with asymptomatic gross hematuria, subsequently diagnosed with three concurrent malignancies: papillary renal cell carcinoma(T1bN0M0), verrucous carcinoma of the renal pelvis (T1N0M0), and low-grade invasive urothelial carcinoma of the ureter (T2N0M0). Comprehensive imaging evaluation revealed a 5.7*5.2cm renal mass and 12cm ureteral tumor extending into the bladder. Following radical nephroureterectomy, histopathological confirmation of three distinct primary malignancies was achieved. Postoperative surveillance identified metastatic progression to adrenal, retroperitoneal, and peritoneal regions within four months, with subsequent development of bladder urothelial carcinoma. The unusual coexistence of three histologically distinct upper urinary tract malignancies, particularly the rare verrucous carcinoma variant, provides novel insights into tumor biology and clinical management paradigms for genitourinary MPMNs.